Capturing Law Reform in The Digital Age: Indonesian and Estonian Perspectives - Sholahuddin Al-Fatih; Sara Sinha (Indonesia Law Reform Journal, 2024)
This article examines how law reform in the digital age happens in Indonesia and Estonia. Indonesia and Estonia are located in different cultures and also areas. While law reform in the digital age happens, the two countries above will also demonstrate differences. This article uses normative legal studies to capture which legal instrument is better in both countries. This article found that Estonia is leading in providing legal instruments to face the digital age, while Indonesia needs to catch up. Some legal instruments in Indonesia such as AI law, Digital ID law, and e-government law should be drafted and implemented.